2015
DOI: 10.2147/jir.s75484
|View full text |Cite
|
Sign up to set email alerts
|

An extract of the medicinal plant Artemisia annua modulates production of inflammatory markers in activated neutrophils

Abstract: PurposeTo investigate the ability of a commercial extract from the medicinal plant Artemisia annua to modulate production of the cytokine, tumor necrosis factor-alpha (TNF-α), and the cyclooxygenase (COX) inflammatory marker, prostaglandin E2 (PGE2) in activated neutrophils.MethodsNeutrophils were harvested from rat whole blood and cultured in the presence of plant extract or control samples. Neutrophils, except unactivated control cells, were activated with 10 μg/mL lipopolysaccharide (LPS). The cells were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…The decrease in PGE 2 production was also observed with a methanol extract of a leaf mixture of A. argyi and A. princeps, an ethanol extract of A. asiatica Nakai, and a supercritical carbon dioxide extract of A. annua. These findings support the prevailing anti-inflammatory activity of Artemisia species, including A. montana, through the suppression of PGE 2 production (Hunt, Yoshida, Davis, Greenhill, & Davis, 2015;Jeong et al, 2014;Yun et al, 2016).…”
Section: Inhibition Of Cox-2 Expression and Pge 2 Productionsupporting
confidence: 82%
“…The decrease in PGE 2 production was also observed with a methanol extract of a leaf mixture of A. argyi and A. princeps, an ethanol extract of A. asiatica Nakai, and a supercritical carbon dioxide extract of A. annua. These findings support the prevailing anti-inflammatory activity of Artemisia species, including A. montana, through the suppression of PGE 2 production (Hunt, Yoshida, Davis, Greenhill, & Davis, 2015;Jeong et al, 2014;Yun et al, 2016).…”
Section: Inhibition Of Cox-2 Expression and Pge 2 Productionsupporting
confidence: 82%
“…Regarding the anti-inflammatory action, it has been observed that all AA derivatives inhibit the action of "mitogen-activated protein kinase" (MAPK), inhibit the transcription factor "nuclear factor kappa-B" (NF-κB), and inhibit the expression of the "Toll-Like Receptor" (TLR4 and TLR9) [11,12]. In addition, AA extracts in ethanol exhibit greater amounts of ART and exhibit a greater ability to block the inflammatory response induced by lipopolysaccharide (LPS) [13]. Furthermore, the phyto-extracts of AA were found to be effective in inhibiting the production of nitric oxide (NO), prostaglandins E2, and inflammatory cytokines (IL-1β and IL-6) in macrophage cultures under the pro-inflammatory stimulus elicited by LPS [13].…”
Section: Introductionmentioning
confidence: 99%
“…Artemisinin delivered directly from the consumption of A. annua leaf powder is highly bioavailable and distributes through peripheral blood and into a plethora of organs including lungs, liver, heart, and brain (Desrosiers et al 2020). Furthermore, both artemisinins and the plant A. annua reduce levels of inflammatory cytokines including IL-6 and TNF-α in vivo (Desrosiers et al 2020; Hunt et al 2015; Shi et al 2015). These effector molecules can be problematic during the “cytokine storm” suffered by many SARS-CoV-2 patients (Schett et al 2020).…”
Section: Introductionmentioning
confidence: 99%